Impact of colourism in social media advertisements on university students' attitude and purchasing behaviour - Toh, Yan Tong (2024)
With the rapid rise of social media, social media advertising has become a crucial role in the online marketing environment, especially among university students, with the help of Internet connection, they prefer to buy products in online stores rather than traditional stores. However, social media advertising tends to convey the message that fair skin is the ideal standard for beauty. The dark skin is portrayed in a negative light, ugly and considered unattractive in appearance. It has opened the eyes of many people, especially university students see the issue such as colourism. This study focuses on the impact of colourism in social media advertisements on university students’ attitude and purchasing behaviour. This study used online survey questionnaire method to gather information through Google Forms.